Board Attributes, Risk Management Committee and Survival of Listed Manufacturing Firms in Nigeria - Labija Amana, Yusuf; Magaji Barde , Ibrahim; Suleiman Kantudu, Aliyu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The dynamics and makeup of a company's board play an important role in determining its success and overall survival. This is due to the crucial role boards play in shaping a company's strategic decisions, risk management, and overall governance. The particular attributes of the board that support long-term company survival, however, are still unknown because research in this area produced contradictory results without taking into account conditions that can strengthen the correlations between the variables. Therefore, this study investigates the moderating effect of risk management committee on the relationship between board attributes and survival of listed manufacturing firms in Nigeria. The study utilized secondary data extracted from annual reports and accounts of 34 sampled firms for the period from 2011 to 2022. The Generalized Least Square (GLS) regression techniques were used for the analysis. The results show that while board independence and board size were negatively associated with survival, greater board expertise enhances firm survival. Similarly, findings reveal that the existence of a risk management committee (RMC) did not only significantly contribute to survival but also moderates the relationship between board attributes and survival of listed manufacturing firms in Nigeria. Thus, the study recommends, amongst others, that the shareholders of listed manufacturing firms in Nigeria should consider reducing the size of the boards to a more manageable and effective number since smaller boards can make decisions more efficiently and prevent conflicts arising from an overly large board.